Implementasi Sistem Sensor Aliran Air Otomatis di Rumah dengan Notifikasi Telegram Berbasis Internet of Things (IoT): Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan - Afiludin, Ahmad yoga (Jurnal Ilmu Komputer dan Teknologi Informasi, 2026)
Water is a highly valuable and limited natural resource. To increase awareness of the global water crisis, it is important to minimize water wastage. With a water flow monitoring system, water resource management can be carried out more efficiently while ensuring fair water distribution. In this research, problems are often encountered in accurately measuring, controlling, and monitoring water usage. These issues can be caused by excessive water consumption, which may lead to losses. Based on these problems, a system was designed to provide notifications of water usage, enabling users to control water consumption, including the ability to remotely turn the water tap on or off. This study presents an innovative solution in the form of an intelligent water monitoring system using a Water Flow Sensor capable of calculating water discharge and a Motorized Ball Valve to automatically control the water tap based on Internet of Things (IoT) technology. To determine the accuracy of the Water Flow Sensor, experiments were conducted by comparing the water volume measured by the sensor with the volume measured using a graduated cylinder.